Therapeutic Pitfalls of Nicardipine (Calcium Channel Blocker) in Hypertensive Emergency with Low Ventricular Ejection Fraction: A Case Of Refractory Cardiogenic Shock - Sukmara, Uta Provinsiana; Mulyawan, Nabila (Journal of Language and Health, 2025)
Nicardipine, a member of the dihydropyridine class of calcium channel blockers, is frequently employed for acute blood pressure control in hypertensive emergencies due to its potent and rapid vasodilatory effects. However, its use in patients with compromised cardiac function particularly those with significantly diminished left ventricular ejection fraction (LVEF) warrants caution, given its potential to depress myocardial contractility. This report presents the clinical course of a 72-year-old female patient with long-standing coronary artery disease and chronically reduced LVEF who was admitted in hypertensive crisis accompanied by respiratory failure. This study seeks to explore and understand the effects of intravenous nicardipine on vulnerable patients whose hearts are already weakend particulary those with severaly reduced left ventricular ejection fraction (LVEF). She was administered intravenous nicardipine at a conservative starting dose of 2 mg/hour. Within six hours, the blood pressure dropped precipitously from 252/138 mmHg to 88/46 mmHg. Despite prompt discontinuation of the drug and initiation of vasopressor support with norepinephrine and dobutamine, the patient’s condition rapidly worsened, progressing to cardiogenic shock and culminating in cardiac arrest on the sixth day in the intensive care unit. This case exemplifies the potential dangers of administering vasodilatory agents like nicardipine to patients with severely limited myocardial reserve. The convergence of systemic vasodilation, reduced inotropic support, and poor compensatory response likely precipitated the hemodynamic collapse.